CaeMmCom – Corpus altaegyptischer multimodaler Communication. Der Aufbau einer multimodalen Datensammlung altägyptischer Kommunikate - Rebecca Döhl; Silvia Kutscher; Jens-Martin Loebel (Zeitschrift für digitale Geisteswissenschaften)
The article describes the implementation of a new digital method for researching multimodal graphic communication for Egyptology. The focus is on the construction of a digital corpus, which collects data for graphic communication and develops methods to systematically describe, annotate and visualise texts, images, and text-image-compositions, as well as their spatial meaning. This is intended to break new ground in the subject in order to identify and understand media and cultural conditions and developments from a synchronous (e.g. genre types) and from a diachronic perspective (e.g. genesis and development of genres).